Relationships between Organic Matter Content in Seawater and Sediment in the East Coast of Bengkalis Island, Riau. Issue 1 (1st December 2022) - Amin, B; Lestari, A; Nurrachmi, I; Nursyirwani, N
Abstract: Organic matter is one of indicators of environmental fertility in both land and aquatic ecosystem. In the coastal area, the content of organic matter in a certain amount can be useful for aquatic biota, but it can also cause a disturbance if the amount exceeds the assimilation capacity of the waters. This study aims to determine the organic matter content in the water column and sediment at high and low tide conditions in the waters of the East coast of Bengkalis Island as well as to determine their relationships. The study was carried out by survey method where samples and data were collected directly in the field and then were taken to the laboratory for further analysis. The results showed that the mean organic matter content in the seawater was lower at high tide (17.38 mg/L – 25.28 mg/L) than at low tide (29.63 mg/L – 35.55 mg/L), whilst in sediments the organic matter content at high tide conditions was also lower (2.28% - 5.37%) compared to low tide (3.46% - 8.62%). The sediment of the east coast of Bengkalis Island was dominated by mud type (53.62 - 93.94 %). The organic matter content in seawater and sediment showed a strong correlation with r value of 0.730 both during high tide (Y= -1.423 + 0.271X) and also during low tide (Y= -14.912 + 0.615X with r value of 0.844), respectively. Further study is still needed to provide a comprehensive understanding on the sustainable environmental condition of the east coast of Bengkalis Island as it is one of the important fishing ground.